Tetrameric complexes of human histocompatibility leukocyte antigen (HLA)-G bind to peripheral blood myelomonocytic cells. - Allan, D; Colonna, M; Lanier, L; Churakova, T; Abrams, J; Ellis, SA; Mcmichael, A; Braud, V (1999)
The nonclassical MHC class I molecule human histocompatibility leukocyte antigen (HLA)-G is selectively expressed on fetal trophoblast tissue at the maternal-fetal interface in pregnancy. It has long been suggested that HLA-G may inhibit maternal natural killer (NK) cells through interaction with particular NK cell receptors (KIRs). To investigate interactions of HLA-G, we constructed phycoerythrin-labeled tetrameric complexes of HLA-G refolded with a self-peptide. These HLA-G tetramers failed to bind to NK cells and cells transfected with CD94/NKG2 and killer immunoglobulin-like NK receptors. In contrast, HLA-G tetramers did bind to peripheral blood monocytes, staining a CD16(+)CD14(mid) subset with greater intensity. On transfectants, HLA-G tetramers bound to inhibitory immunoglobulin-like transcript (ILT)2 and ILT4 receptors. However, staining in the presence of antibodies reactive with ILT receptors revealed that the interaction of HLA-G tetramers with blood monocytes was largely due to binding to ILT4. These results suggest that the primary role of HLA-G may be the modulation of myelomonocytic cell behavior in pregnancy.